Poor radiological outcomes and associated factors among tibial shaft fracture patients treated with intramedullary nail fixation at Addis Ababa Burn, Emergency and Trauma Hospital, Ethiopia - Shugie, Yohannes; Kebede, Samuel; Adugna, Fanna; Demissie, Dereje Bayissa; Desta, Tilahun (Frontiers in Surgery, 2025)
BackgroundTibial shaft fractures account for the majority of operatively treated long bone fractures and have the greatest prevalence of open wounds. For both open and closed injuries, intramedullary fixation has become the standard of therapy. At Addis Ababa Burn, Emergency, and Trauma (AaBET) Hospital, the rates of poor radiological outcomes for tibial shaft fractures treated with intramedullary fixation are unknown.MethodsA retrospective health facility-based cross-sectional study design was conducted among patients with tibial shaft fractures treated with intramedullary nails at AaBET Hospital. Data were collected by reviewing medical records and x-rays. The study was conducted on a sample size of 160 using a simple random sampling technique. Descriptive statistics such as frequency and percentage were used to summarize the results. Binary logistic regression was used to describe the associations between variables. A P-value < 0.05 was considered statistically significant.ResultsThis study included 122 (76.3%) men and 38 (23.8%) women with a mean age of 36.3 ± 13.9. The magnitude of poor radiological outcomes among the tibial shaft fracture patients treated with intramedullary nail fixation was 23.1%, with factors including include the presence of medical comorbidity [adjusted odd ratio (AOR) (95% confidence interval, CI): 16.5 (2.524–108.69)], having diabetes mellitus [AOR (95% CI): 3.85 (1.07–14.08)], Gustilo–Anderson type III (GA III) open fractures [AOR (95% CI): 17.4 (3.11–97.72)], and post-operative infection [AOR (95% CI): 13.9 (5.8–33.16)] identified as being significantly associated with poor radiological outcomes.ConclusionThe magnitude of poor radiological outcomes in this study is comparable to other similar studies. The study found that factors including Gustilo–Anderson type III open fractures, diabetes mellitus, and post-operative infections increase the odds of poor radiological outcomes in patients with tibial shaft fractures after intramedullary nailing. Therefore, surgeons should improve their assessment and evaluation of patients with infection signs and use negative wound pressure for GA III fractures.